2015
DOI: 10.1016/j.jhep.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

A CCRK-EZH2 epigenetic circuitry drives hepatocarcinogenesis and associates with tumor recurrence and poor survival of patients

Abstract: These findings uncover an epigenetic vicious cycle in hepatocarcinogenesis that operates through reciprocal regulation of CCRK and EZH2, providing novel therapeutic strategy for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 34 publications
2
63
0
Order By: Relevance
“…Being a key member of the Drosophila Polycomb group (PcG), EZH2 plays a crucial role in gene expression regulation, maintenance of cell identity, stem cell renewal and oncogenesis. Recent studies have shown that EZH2 overexpression predicts poor patient prognosis and is a frequent event in various cancers, such as breast cancer [1], malignant prostate cancer [2], and hepatocellular carcinoma [3]. There are reports depicting the expression and oncogenic role of EZH2 in lung tumorigenesis [4,5] and EZH2 has been suggested to modulate several pathophysiological processes by promoting cell proliferation and cell cycle progression [6], accelerating cell infiltration and metastasis [7], and inhibiting apoptosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Being a key member of the Drosophila Polycomb group (PcG), EZH2 plays a crucial role in gene expression regulation, maintenance of cell identity, stem cell renewal and oncogenesis. Recent studies have shown that EZH2 overexpression predicts poor patient prognosis and is a frequent event in various cancers, such as breast cancer [1], malignant prostate cancer [2], and hepatocellular carcinoma [3]. There are reports depicting the expression and oncogenic role of EZH2 in lung tumorigenesis [4,5] and EZH2 has been suggested to modulate several pathophysiological processes by promoting cell proliferation and cell cycle progression [6], accelerating cell infiltration and metastasis [7], and inhibiting apoptosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…35, 36 Furthermore, EZH2 and AKT could influence expression of each other indicating that they constituted a positive loop. 21, 37, 38, 39 In addition, one-fifth of all human lncRNAs identified is physically associated with EZH2. 18, 19 Here, gain and loss of UCA1 assay in GC cell has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Lentiviruses encoding shRNA against Hdac8 (shHdac8) or control sequence (shCtrl) were packaged according to the manufacturer's instructions (Dharmacon) for transduction in the dietary obesity models. At the age of 6 and 18 weeks, 5 Â 10 7 transducing units of lentiviruses in 100 mL PBS were administered via tail vein injection as previously described (17,18). Intraperitoneal glucose or insulin tolerance test (IPGTT/IPITT) was performed at the age of 26 weeks.…”
Section: Lentiviral-mediated Shrna Knockdown In Obesity-promoted Nashmentioning
confidence: 99%